The Validity and Reliability of the Sinhala Translation of the Patient Health Questionnaire (PHQ-9) and PHQ-2 Screener - Hanwella, Raveen; Ekanayake, Shakya; De Silva, V.A. (Wiley, 2014)
The Patient Health Questionnaire (PHQ-9) was adapted and translated into Sinhala. Sample consisted of 75 participants diagnosed with MDD according to DSM-IV criteria and 75 gender matched controls. Concurrent validity was assessed by correlating total score of PHQ-9 with that of Centre for Epidemiological Studies Depression Scale (CESD). The Structured Clinical Interview for DSM-IV (SCID-II) conducted by a psychiatrist was the gold standard. Mean age of the sample was 33.0 years. There were 91 females (60.7%). There was significant difference in the mean PHQ-9 scores between cases (14.71) and controls (2.55) (P < 0.001). The specificity of the categorical algorithm was 0.97; the sensitivity was 0.58. Receiver operating characteristic (ROC) analysis found that cut-off score of ≥10 had sensitivity of 0.75 and specificity of 0.97. The area under the curve (AOC) was 0.93. The sensitivity of the two-item screener (PHQ-2) was 0.80 and the specificity was 0.97. Cronbach's alpha was 0.90. The PHQ-9 is a valid and reliable instrument for diagnosing MDD in a non-Western population. The threshold algorithm is recommended for screening rather than the categorical algorithm. The PHQ-2 screener has good sensitivity and specificity and is recommended as a quick screening instrument.
Keywords: Patient Health Questionnaire